1996
DOI: 10.1161/01.hyp.27.3.514
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B Is a Prorenin Processing Enzyme

Abstract: Conversion of prorenin to renin results from proteolytic cleavage of a 43-amino-acid prorenin prosegment in renal juxtaglomerular cells. The enzyme that performs this processing is not known. Of several enzymes proposed, cathepsin B is a candidate because it colocalizes with renin in juxtaglomerular cell secretory granules and accurately cleaves the prosegment of human prorenin in vitro. It is not known whether cathepsin B can perform this function in the cell. We examined this using secretory granule-containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 27 publications
0
46
0
Order By: Relevance
“…About 80% of intracellular renin has little or no enzymatic activity and is called inactive renin or prorenin (2). Inactive renin can be converted into the active form through limited proteolysis at physiological pH by tissue proteases such as trypsin and kallikreins (3,4), but probably by cathepsin B in vivo (5).…”
Section: Introductionmentioning
confidence: 99%
“…About 80% of intracellular renin has little or no enzymatic activity and is called inactive renin or prorenin (2). Inactive renin can be converted into the active form through limited proteolysis at physiological pH by tissue proteases such as trypsin and kallikreins (3,4), but probably by cathepsin B in vivo (5).…”
Section: Introductionmentioning
confidence: 99%
“…However, many tissues have enzymes other than ACE that are capable of converting angiotensin I into Ang II (Figure 4). For instance, the heart expresses tonins, cathepsins, chymases and trypsin that can synthesize Ang II from Ang I [Hollenberg et al 1998;Neves et al 1996;Kramkowski et al 2006]. As a result; attempts to inhibit the RAS could fail to induce the desired effects on vasoconstriction and on renal sodium excretion.…”
Section: Aceis Arbs and Direct Renin Inhibitors: Differential Featuresmentioning
confidence: 99%
“…It was known for some time that a number of enzymes exhibited the capability of processing prorenin to active renin in vitro, e.g., cathepsins B, D, and G, tissue kallikrein, convertases, trypsin, mouse submandibular gland prorenin converting enzyme, plasmin, pepsin, and others (2,6,10,14,17,18). However, there were issues of proteolysis causing degradation or issues regarding the colocalization of the enzymes with renin in vivo, which lead to uncertainty about their roles.…”
mentioning
confidence: 99%
“…Neves et al (18) showed that cotransfection of cathepsin B and human preprorenin expression vectors into secretory granule-containing rat GH4C1 cells resulted in enhanced generation of secretable active renin relative to the preprorenin vector alone. This suggests that cathepsin B could localize to the appropriate cellular compartment to effect correct processing in an intact cell.…”
mentioning
confidence: 99%